Unexpected case of ankle tuberculosis in a young professionals leading to delay in diagnosis - Mohd Yusof, Nazri; Zakaria@Mohamad, Zamzuri; How, Soon Hin (2015)
We report a case of a 38 year-old engineer presented with left ankle pain for 2 years and initially treated as gouty arthritis because of high serum uric acid. A year later his left ankle become swollen and plain radiograph showed soft tissue swelling around the ankle with normal articular surface and bone. An MRI investigation reported as gouty arthritis of ankle with tophi. While on treatment for gouty arthritis, he developed pus discharge from the swelling. The ankle pain also worsen and he was unable to weight bear on the affected leg. An incision and drainage shown pus from the ankle joint which grew pseudomonas aeruginosa. He was treated with intravenous followed by oral ciprofloxacin 250 mg bd. However his condition does not improved and a month after antibiotic treatment a repeated radiograph shows narrowing of joint space with irregular cortical destruction, osteopenic bone . suggestive of worsening of his septic arthritis. During this period he deny of having any fever, cough or night sweats. However he did notice some loss of weight and loss of appetite. He has worked in Africa and Russia before in petroleum industry. After 4 months of antibiotic and no sign of improvement, a biopsy and repeat culture was taken from the ankle which reveal tuberculous arthritis and positive for AFB culture. A plain chest radiograph revealed miliary tuberculosis picture. He was started on a anti TB treatment and the wound healed after a few weeks. After 4 months of treatment he was able to walk without support with reduce ankle range of motion. This case illustrate that the diagnosis was delay because tuberculosis was not suspected in a young professionals with ankle pain and elevated serum uric acid level. Further delay in diagnosis because MRI report also suggestive of gouty tophi and the pus culture and sensitivity grew pseudomonas aeruginosa.